Differences in early auditory exposure across neonatal environments. (September 2019) - Liszka, Lara; Smith, Joan; Mathur, Amit; Schlaggar, Bradley L.; Colditz, Graham; Pineda, Roberta
Abstract: Background: To date, no study has compared preterm and full term auditory environments. Aim: To define differences in auditory exposure for preterm infants at term equivalent age in the neonatal intensive care unit (NICU) compared to auditory exposure in hospital rooms on a labor and delivery ward after full term birth. Study design: Ninety-eight infants (48 preterm infants born 28 weeks gestation in the NICU at term equivalent age and 50 full term infants in a hospital room on the labor and delivery ward within 4 days of birth) had auditory exposure measured over a single 16-hour period using the Language Environment Acquisition (LENA) device. Results: More language ( p < 0.001) was observed on the labor and delivery ward than in the NICU, with an average of 3.3 h more language in a 16-hour period and an average of 14, 110 more words spoken around infants in a 16-hour period on the labor and delivery ward ( p < 0.001). More electronic sounds were observed in the NICU, with an average of 2.3 h more in the 16-hour period ( p < 0.001). The average decibel level in the NICU was lower than in the hospital rooms on the labor and delivery ward (57.16 ± 2.30 dB, compared to 63.31 ± 2.22 dB; p < 0.001). Conclusion: The NICU auditory environment for preterm infants is different than the auditory environment for full term infants, with less language, more electronic sounds, and quieter stimuli. This understanding can aid in developing appropriate interventions that enhance positive forms of auditory exposures. Highlights: There are differences in full term and preterm auditory environments at term. Less language was observed in the NICU than on the labor and delivery ward. More electronic sound was observed in the NICU than the labor and delivery ward. The NICU had quieter stimuli than the labor and delivery ward.